Beyond Calories: Understanding India’s Changing Nutritional Landscape - Padam Singh (Journal of the Indian Society of Agricultural Statistics, 2026)
India has achieved substantial progress in agricultural production and food availability over recent decades. However, a steady decline in reported per capita calorie intake across successive National Sample Survey (NSS) rounds has raised concerns, particularly as calorie intake remains a key indicator in global hunger assessments. This apparent paradox has led to questions about whether declining calorie consumption reflects worsening nutritional status or broader structural changes in the population.This paper examines trends in calorie intake alongside shifts in dietary patterns, Recommended Dietary Allowances (RDA), minimum dietary energy requirements (MDER), and evidence from national surveys such as NNMB and NFHS. Over time, RDA revisions indicate reduced energy requirements due to declining physical activity, urbanization, and mechanization. Concurrently, diets have diversified, moving away from cerealheavy consumption toward increased intake of milk, fats, fruits, and animal-source foods.Data show a reduction in the proportion of households consuming below 1800 kcal per capita per day. Moreover, a notable share of individuals reporting lower calorie intake exhibit overweight, obesity, hypertension, and dyslipidaemia, suggesting that lower intake may reflect conscious dietary moderation rather than deprivation. Anthropometric trends further support this, with improvements in adult BMI profiles and reductions in child undernutrition.The findings indicate that declining calorie intake in India should not be interpreted in isolation as evidence of rising hunger. Instead, it reflects changing energy needs, dietary transitions, and health-driven behavioural shifts. Calorie-based indicators alone are inadequate; a multidimensional approach incorporating dietary quality, anthropometry, metabolic health, and access is essential for accurately assessing nutritional status.